Media Edukatif Interaktif Berbasis Nilai-Nilai Islam Untuk Menumbuhkan Karakter Religius Anak Usia Dini Di Tab Syuhada’ Haji Blitar - Choirul Hidayah; Miftakhul Rohman; Arif Muzayin Shofwan; Alaiya Choiril Mufidah (Universitas Nahdlatul Ulama Blitar, 2025)
Interactive Educational Media Based on Islamic Values to Foster the Religious Character of Early Childhood at TAB Syuhada’ Haji, Blitar. This study aims to describe the implementation of interactive educational media based on Islamic values in fostering the religious character of early childhood learners at Taman Asuh Bayi (TAB) Syuhada’ Haji, Blitar City. The research employed a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The focus of the study was directed toward the use of learning media that integrate Islamic values through prayer activities, exemplary stories of the prophets, introduction to hijaiyah letters, habituation of worship practices, and thematic play activities in accordance with the developmental characteristics of early childhood.The findings indicate that interactive educational media based on Islamic values are able to increase children’s active engagement in the learning process and facilitate the internalization of religious values in a natural and sustainable manner. Children demonstrated the development of religious character traits such as gratitude, discipline in worship, polite and respectful behavior, and a sense of love for Allah and His Messenger. The media used were simple, contextual, and made use of the surrounding environment, thereby making the learning process more meaningful.This study concludes that the use of interactive educational media grounded in Islamic values plays a significant role in shaping the religious character of early childhood learners and can be considered an effective strategy for character-based early childhood education.